Unravelling Potential Mechanisms of Piper retrofractum Vahl. Bioactive Compounds as Cervical Cancer Chemopreventive Agent by Bioinformatic Approach - Mahindra, I Kadek Sindhu Satya; Kusuma, I Made Gede Ari; Sari, Wayan Dianda; Diantari, Desak Made Dewi; Lestari, Priyanka; Santika, I Wayan Martadi (Indonesian Journal of Cancer Chemoprevention, 2024)
Cervical cancer is the leading cause of cancer death after breast cancer. HPV infection is the main cause of cervical cancer which will cause overexpression of E6 oncoprotein. E6 oncogene can cause cancer cells to continue to proliferate. Long pepper fruit (Piper retrofractum Vahl.) has antioxidant activity and contains piperine compounds that have anticancer activity. This study aims to assess the potential of long pepper fruit extract as a chemopreventive agent for cervical cancer. The research method was conducted by in silico assay with network pharmacology and molecular docking analysis. We found five hub genes including HSP90AA1, SRC, AKT1, STAT3, and PIK3CA. KEGG analysis showed that the most dominant signaling pathways involved are neuroactive ligand-receptor interaction, PI3K-Akt signaling pathway, MAPK signaling pathway, Calcium signaling pathway, and cAMP signaling pathway. Through molecular docking, it was found that long pepper fruit has the potential to inhibit the E6 oncogene of HPV. Based on the research results, long pepper fruit extract may has the potential as a chemoprevention agent for cervical cancer.Keywords: Cervical cancer, oncoprotein HPV16-E6, Piper retrofractum Vahl., molecular docking, network pharmacology.